The effects of nano‐curcumin supplementation on glycemic control, blood pressure, lipid profile, and insulin resistance in patients with the metabolic syndrome: A randomized, double‐blind clinical trial. (13th April 2021) - Bateni, Zohre; Rahimi, Hamid Reza; Hedayati, Mehdi; Afsharian, Shila; Goudarzi, Razieh; Sohrab, Golbon
Abstract : Metabolic syndrome (MetS) is one of the most important health hazards. Curcumin is extracted from Curcuma longa (turmeric), which can affect the components of MetS. To increase the oral bioavailability of curcumin, nano‐micelle curcumin is used instead of curcumin powder. In this randomized, double‐blind, controlled clinical trial, 50 patients with MetS were randomly assigned to two groups to receive either 80 mg/day nano‐curcumin ( n = 25) or placebo ( n = 25), for 12 weeks anthropometric measurements, blood pressure, and biochemical factors—including fasting blood sugar (FBS), Hemoglobin A1c (HbA1c), homeostatic model assessment (HOMA) for insulin resistance (HOMA‐IR), pancreatic β cell function (HOMA‐β) and lipid profile—were assessed at the baseline and the end of the study. Statistical analyses were done using SPSS software (Version 23). The analysis between the two groups has illustrated a significant reduction in the average change of triglyceride (TG) levels (−60.5 ± 121.7 vs. 13.1 ± 78.1 mg/dL; p < .05) and HOMA‐β (−5.7 ± 48.2 vs. −4.01 ± 16.9; p < .05). But there were no significant differences in anthropometric measurements, blood pressure and biochemical factors—including FBS, HbA1c, HOMA‐IR, HOMA‐β, and lipid profile variables include (total cholesterol, LDL‐C, and HDL‐C) at the end of the study. In conclusion, supplementation with nano‐micelle curcumin significantly improved serum TG in MetS patients.